COMPARATIVE ANALYSIS OF WATERSHED CHARACTERISTICS IN BALI PROVINCE FOR SUSTAINABLE WATER RESOURCES MANAGEMENT - I Gusti Agung Putu Eryani; Abd Muluk Abd Manan; Made Widya Jayantari (INDONESIAN JOURNAL OF URBAN AND ENVIRONMENTAL TECHNOLOGY, 2021)
Aims: This research will provide an overview of the comparative analysis of watershed characteristics in Bali which are differentiated from watersheds flowing to the north, and watersheds flowing to the south of Bali Province. The aim is to determine the characteristics of each, and proper sustainable management for each watershed. Methodology and Results: This is a descriptive, quantitative research that analyzes and compares the characteristics of the Saba watershed and Unda watershed, where the characteristics analyzed are morphometric and hydrological.  From the analysis, it was observed that the Unda watershed, which has a flow direction to the south of the island of Bali, and the Saba watershed, flowing to the north of the island of Bali, possess several differences and similarities. The similarities include rainfall patterns, high temperatures, and the comparison values between Qmax and Qmin is significant. Meanwhile, the differences include the Saba watershed slope being steeper than the Unda watershed, and the Saba has young geomorphic features, while the Unda watershed possesses advanced geomorphic features. Conclusion, significance, and impact of study: Differences in watershed characteristics lead to differences in the management carried out. Furthermore, in terms of hydrology, where there are lesser differences, the sustainable management of the Saba and Unda Watershed also require conservation in form of a reservoir (weir or dam). This is to enable the storage of water in the rainy period for the dry season.